Divergent: A Corpus-Assisted Semantic/Semiotic Study of 'Eresia', “Heresy”, in Contemporary Written Italian - Caterina Guardamagna (Modern Languages Open)
This article offers a corpus-assisted lexical semantic/semiotic analysis of the noun eresia “heresy” in contemporary written Italian. By adopting a qualitative and quantitative approach and drawing on the theoretical resources of both structuralist-inspired semiotics and poststructuralist/Peircean semiotics, this study reveals that eresia has a complex meaning spanning across religious and non-religious domains. Crucial is the idea of “deviation”, stretching into the intersubjective domain, where it marks interpersonal coordination by signalling communal common ground and extended intersubjectivity. This article also includes theoretical and methodological reflections on the role of collocations in the relatively young field of corpus-assisted semiotic analysis.